Revisit e-procurement practices during MCO due to COVID-19 pandemic / Ronn Rowell Roangis @ Rojis - Roangis @ Rojis, Ronn Rowell (2021)
E-procurement is one of government initiatives under eGovernment application. E-procurement was introduced to replace manual procurement system in public agencies to systematic procurement which using internet as platform of transaction. However, in the early year 2020, a new virus called COVID-19 has spread all over the world and has affected communities globally,with more than 180 million reported cases as of June 2021. Construction industry is highly affected due to Covid-19 pandemic outbreak that caused slightly shift in project timeline and changes in working approach. Thus, this research is to study the experience and challenges faced by contractors using e-procurement during this pandemic head-up. This research will help to identify e-Procurement practices and in Sabah.